Patient-Reported Incident Measure (PRIM) tools for reporting patient safety incidents: protocol for a scoping review - Mercè Soler Font; Ignacio Ferreira-Gonzalez; Ignasi Bolíbar; Maria Rubio-Valera; Merce Soler-Font; Víctor Quirós González; Karla Salas-Gama; Dimelza Osorio; Maria Nieves Plana; Julio Muñoz-Miguel; Maria Teresa Franco; Mariona Secanell-Espluga; et al. (BMJ Open, 2025)
Introduction Patient safety incidents during healthcare cause a high burden and mortality, but many go unreported. Involving patients and caregivers in the identification and reporting of safety incidents would add value to the current incident reporting systems used by health professionals. Identifying and analysing patient safety incidents is essential to prevent future events, allowing organisations to apply a learning-from-error approach and to implement improvement plans. Patient-Reported Incident Measures are tools for patients and caregivers to report safety issues related to their healthcare. In accordance with WHO’s patient safety taxonomy, the term patient safety incidents is used throughout this protocol to encompass events that do and do not reach the patient, including what are commonly referred to as near misses and adverse events. We aim to identify and describe the published literature about tools for patients or caregivers to report patient safety incidents in healthcare.Methods and analysis We will conduct a scoping review. We have developed inclusion criteria using the PCC (population, concept and context) format, where population includes adult patients or caregivers; concept refers to documents describing formal tools used to report patient safety incidents; and context includes any healthcare setting, such as hospitals or mental health centres, during or immediately after care. The scoping review will be reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines. Evidence sources include primary research, systematic reviews, meta-analyses, conference abstracts, letters, guidelines, as well as policy documents, reports, blogs and websites, without language restriction. An initial database search in Medline, Embase, CINAHL, and Cochrane Library from database inception up to June 2023 identified 4500 initial citations, of which 4103 were selected for evaluation after duplicates were removed. We will supplement the search by checking the reference lists of included studies for additional sources of evidence and an additional search in Google to identify non-peer-reviewed documents. This initial search will be updated before completing the review. We will use a self-created data collection form for data extraction and perform a narrative synthesis to integrate and summarise the review findings. We will describe the general characteristics of the tool: setting, scope, format, content, type of patient safety incident and severity, the moment of notification, relation to patient safety incident reporting and learning systems, development process, testing, validation, or piloting, among other characteristics. As a result of this scoping review, we intend to provide an index of patient/caregiver-reported safety notification tools and a list of descriptive or evaluation studies.Ethics and dissemination We will only use published data. Approval from the human research ethics committee is not required. The results of this scoping review will be submitted for publication in an international peer-reviewed journal and scientific meetings. Findings will also be disseminated through digital science platforms and academic social media.